Representation Signs of Post-Traumatic Stress Disorder in Smile Film by Parker Finn: A Semiotic Analysis of Charles Sanders Pierce - Ayub, Amelia Mulyani (Lakon : Jurnal Kajian Sastra dan Budaya, 2023)
Abstract: This research focuses on understanding the signs that portray Post-Traumatic Stress Disorder in the film Smile, employing Charles Sander Pierce's triadic sign theory framework, encompassing Representamen, Object, and Interpretant. The research methodology employed is a qualitative descriptive approach, with textual and visual data forming the basis for analysis. The primary data sources include images and transcripts from the film Smile, released in 2022. The film Smile, directed by Parker Finn, was chosen as the representative work due to its successful portrayal of an individual's experience with Post Traumatic Stress Disorder. This representation involves various types of signs that depict the psychological state of the character Rose. The analysis is conducted using a sign analysis approach within the context of the film. Through this analysis,  can comprehend how trauma is represented, interpreted, and processed in an individual's mind and emotions through the various signs that manifest in the film.